Analisis pengaruh tingkat pengangguran, pertumbuhan penduduk, tingkat kemiskinan dan indeks pembangunan manusia terhadap pertumbuhan ekonomi di Kabupaten Tanjung Jabung Barat - Muhammad Iqbal; Junaidi Junaidi; Hardiani Hardiani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
This research aims to analyze the conditions and developments in the unemployment rate, population growth, poverty rates and the Human Development Index (HDI) towards economic growth in the West Tanjung Jabung Regency. In addition, it also analyzes the influence of the unemployment rate, population growth, poverty level and Human Development Index (HDI) on economic growth in Tanjung Jabung Barat Regency in 2002-2017. The method of analyzing this research is multiple regression analysis. The results of the research conclude that, economic growth has fluctuated but tends to decline, the unemployment rate fluctuates or fluctuates, population growth decreases, poverty rates tend to decline even though the figure is still high, and the Human Development Index (HDI) continues to increase every year. At the level of recruitment there is no significant influence on economic growth, and population growth also has no significant effect on economic growth. Poverty level and Human Development Index have a significant influence on economic growth in TanjungJabung Barat Regency in 2002-2017.